HUBUNGAN FAKTOR PERAWAT DAN KEBENARAN PENYIAPAN OBAT INJEKSI [THE RELATIONSHIP BETWEEN NURSE FACTORS AND THE CORRECTNESS OF PREPARATION OF INJECTION DRUGS] - Herulim Tarulitua Simamora; Emiliana Tarigan; Emiliana Tjitra (Universitas Pelita Harapan, 2021)
Efforts to ensure patient safety during drug administration are to prevent drug administration errors. The characteristics of the nurse and the five right principles are factors that can ensure patient safety in the hospital. The Ministry of Health stated that there should not be an error in drug administration (0%), which is a very difficult application in the field. One Hospital in West Java has set a rate of <5% per month as the tolerable limit for drug administration errors. The reality in the field is that the average incidence of drug administration errors is still high compared to the set standards, namely 8.2% per month from January to June 2018. The purpose of this study was to analyze the relationship between nurses’ factors and the true incident of injection drug preparation by nurses at one Hospital in West Java. A total of 22 nurses were involved in this study, grouped into nurse 1 who prepared the medication and nurse 2 who applied the Independent Double Check /IDC. Each nurse recorded the results of the five principles of correct injection drug preparation in separate records independently. The results showed that the observed agreement value (Po) and the expected agreement value (Pe) regarding the principle of five steps were very good (> 0.960) but the kappa value among nurses 1 and 2 were in the moderate category (<0.50). In addition, this study revealed that the clinical competence of the nurse 1 was related to the correct injection drug (p = 0.005), their work experience was related to the correct route of drug injection (p = 0.017). It is showed that the drug injection was influenced by the characteristics of nurse 1, especially by the clinical competence (p = 0.046). This study recommends that it is needed of further in-depth analysis of the factors that influence the correctness of drug administration. BAHASA INDONESIA Upaya dalam menjamin keselamatan pasien selama pemberian obat-obatan adalah dengan mencegah terjadinya kesalahan pemberian obat. Karakteristik perawat dan prinsip lima benar merupakan faktor yang bisa menjamin keselamatan pasien di rumah sakit. Kementerian Kesehatan menyatakan bahwa tidak boleh ada kejadian kesalahan pemberian obat (0%), dimana angka tersebut sangat sulit untuk diterapkan di lapangan. Satu rumah sakit di Jawa Barat telah menetapkan angka < 5% per bulan sebagai batas kesalahan pemberian obat yang bisa ditoleransi. Kenyataan dilapangan bahwa rata-rata kejadian kesalahan pemberian obat masih tinggi dibanding standar yang ditetapkan yaitu 8,2% per bulan dari Januari sampai Juni 2018. Tujuan penelitian ini untuk menganalisis hubungan antara faktor perawat dan kejadian kebenaran penyiapan obat injeksi oleh perawat di rawat inap satu rumah sakit di Jawa Barat. Sebanyak 22 perawat terlibat dalam penelitian ini, dikelompokkan menjadi perawat satu yang menyiapkan obat dan perawat dua yang melakukan Independent Double Check/IDC. Setiap perawat mencatat hasil prinsip lima benar penyiapan obat injeksi dalam catatan yang terpisah secara independen. Hasil penelitian menunjukkan nilai kesepakatan teramati dan nilai kesepakatan harapan prinsip lima benar sangat baik (>0,960) namun nilai kappa antara perawat satu dan dua dalam kategori sedang (<0,50). Selain itu, hasil penelitian ini juga menunjukkan bahwa kompetensi klinik perawat satu berhubungan dengan benar obat injeksi (p=0,005), pengalaman kerja perawat satu berhubungan dengan benar rute obat injeksi (p=0,017). Selain itu, hasil penelitian ini menunjukkan bahwa benar obat injeksi dipengaruhi oleh karakteristik perawat satu terutama oleh kompetensi kliniknya (p=0,046). Penelitian ini merekomendasikan analisis lebih mendalam tentang faktor-faktor yang memengaruhi kebenaran pemberianobat.